Hubungan Academic Hardiness dan Psychological Well-being pada Mahasiswa Tingkat Akhir Jurusan Keperawatan yang sedang Menyusun Skripsi - Suprapti, Bhineska Juniar Dwi; Rahayu, Maria Nugraheni Mardi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Final year students who experience difficulties or obstacles while preparing their thesis can interfere with their psychological well-being, one of which is the final year students majoring in nursing. They need a personality that can improve psychological well-being in dealing with pressure when compiling a thesis, namely academic hardiness. This research aims to find the significant relationship between academic hardiness and the psychological well-being of final-year students majoring in nursing who write a thesis. This research uses quantitative methods with a research design correlational. The data collection technique used in this research was accidental sampling. The number of research subjects was 204 participants, with the criteria as final-year students nursing majors who are currently writing a thesis and aged 18 – 25 years. The data collection method uses two scales, namely Ryff Psychological Well-Being Scale (RPWBS) developed by Sasaki et al., (2020) and the Academic Hardiness Scale (AHS) revised by Creed et al., (2013). The research result correlation between academic hardiness and psychological well-being is a significant positive relationship between academic hardiness and psychological well-being. Three dimensions of psychological well-being have a significant positive relationship with academic hardiness, namely environmental mastery environmental mastery, purpose in life and personal growth.